Funkcjonowanie gospodarki rolnej na Zachodniej Białorusi i Zachodniej Ukrainie w latach 1939–1941 w świetle centralnej prasy radzieckiej - Żelazny, Beata (Acta Universitatis Lodziensis. Folia Historica, 2015)
One of the most important part of sovietization policy in the areas of Western Ukraine and Western Belorus were the changes in the structure of the agricultural economy. In this process, an important role was played by the press, which was a kind of relay will of the highest authorities of the Soviet Union. The issue of the functioning of the agricultural economy in the areas of Western Ukraine and Western Belarus was one of the most commented on by the press aspects of these lands. Press took part in the action of promotion of collective agricultural system, describing ,,enthusiasm” of the population of newly connected to the USSR areas for this method of cultivation of the land, and thus to the Soviet regime. According to the image built by the press, kolkhozes were to be testimony to the superiority of the collective agricultural economy over the individual. Joining the kolkhozes, according to the propaganda was voluntary and mass, and working in tchem peasants achieved high crops. The press also presented the values of living in a kolkhoz. In the context of the functioning of the agricultural economy in Western Belarus and Western Ukraine also reported their participation in the All-Union Agricultural Exhibition in 1941 and the issue of the drying so-called marshes of Polesie, which occupied a large part of the Bielorussian SSR.